FREE CONVECTIVE HEAT TRANSFER FROM AN OBJECT AT LOW RAYLEIGH NUMBER (Journal of Mechanical Engineering, 2013)
Free convective heat transfer from a heated object in very large enclosure is investigated in thepresent work. Numerical investigation is conducted to explore the fluid flow and heat transfer behavior in thevery large enclosure with heated object at the bottom. Heat is released from the heated object by naturalconvection. Entrainment is coming from the surrounding. The two dimensional Continuity, Navier-Stokesequation and Energy equation have been solved by the finite difference method. Uniform grids are used in theaxial direction and non-uniform grids are specified in the vertical direction. The differential equations arediscretized using Central difference method and Forward difference method. The discritized equations withproper boundary conditions are sought by SUR method. It has been done on the basis of stream function andvorticity formulation. The flow field is investigated for fluid flowing with Rayleigh numbers in the range of 1.0 ?Ra ? 1.0×103 and Pr=0.71. It is observed that the distortion of flow started at Rayleigh number Ra=10. It isobserved that the average heat transfer remains constant for higher values of Reyleigh number and heatingefficiency varies with Ra upto the value of Ra=35 and beyond this value heating efficiency remains constant.DOI: http://dx.doi.org/10.3329/jme.v43i1.15775